BAGIAN AYAH DAN SAUDARA DALAM KEWARISAN ISLAM DI INDONESIA (Perspektif Fiqh, KHI dan Prakteknya di PA dan Masyarakat) (UINSI Samarinda, 2012)
After the Compilation of Islamic Law, it appears that not only applied Shafi opinion, but wider use other teachings, known as the